Does corporate social responsibility impact firms' innovation capacity? The indirect link between environmental & social governance implementation and innovation performance - Broadstock, David C.; Matousek, Roman; Meyer, Martin; Tzeremes, Nickolaos G. (Elsevier, 2020)
Firms' choices on corporate social responsibility (CSR) and environmental, social and governance (ESG) implementation strategies can arguably have a positive impact on their value and performance. This “doing well by doing good” view remains debated in the literature. Our study contributes to this debate by investigating the impact of firms' engagement in ESG policies on their innovation capacity levels. More specifically, we apply a nonparametric frontier analysis framework to a sample of 320 Japanese firms over the period 2008–2016. Our study provides evidence of a nonlinear relationship between ESG policy adoption and firms' innovation capacity. In other words, our findings are consistent with a process of “indirect value-creation” under which firms' CSR/ESG policy adoption initially enhances their ability to pursue innovation activities and, then, eventually affects positively their value creation and financial/operational performance.
Keywords: Corporate social responsibility (CSR); Environmental, social and governance (ESG); Corporate social performance (CSP); Innovation capacity; Efficiency and productivity; Nonparametric analysis; fi=Tuotantotalous|en=Industrial Management|